APPLICATION OF STANDARD OPERATIONAL PROCEDURES TO THE PERFORMANCE OF PT SATU RODA INDONESIA EMPLOYEES - Satria, Vivanda Ahmad; Christian, Timotius Febry (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This research aims to determine the consistent, efficient and compliant implementation of Standard Operating Procedures (SOP) within the PT Satu Roda Indonesia organization. This study uses a qualitative method. The research will be carried out at the PT office. Satu Roda Indonesia which is located at the Mentari Beach Housing Complex in Surabaya. The sampling method used was purposive sampling. Interviews were conducted with company employees and external company experts to understand the implementation of existing SOPs at PT. Satu Roda Indonesia. In an analysis of the implementation of Standard Operating Procedures (SOP) at PT. Satu Roda Indonesia, several important findings can be concluded that the implementation of Standard Operating Procedures (SOP) at PT Satu Roda Indonesia has proven to be the key to increasing work efficiency and employee performance. By having clear and structured SOPs, employees have clear guidance to carry out their duties consistently and precisely. This reduces confusion and errors in the execution of daily work, which in turn increases productivity and efficiency. SOPs also play a role in ensuring that each step in the work process has been carefully thought out, thereby minimizing wasted time and ensuring that resources are used optimally. By following SOPs, employees can work more efficiently and effectively, because they have clear guidance on what is expected of them in each situation.